PENGARUH PARTISIPASI ANGGARAN, AKUNTANSI PERTANGGUNGJAWABAN DAN MOTIVASI KERJA TERHADAP KINERJA MANAJERIAL : Studi Kasus Pada SKPD Kabupaten Ende - Resi, Hasnawati A; Thalib, Sabra B Wahab; Soleiman, Iriany Dewi (Jurnal Riset Ilmu Akuntansi, 2021)
The purpose of this study was to determine the effect of budgetary participation, responsibility accounting and work motivation on managerial performance in the Ende Regency SKPD. The data collection in this study used a questionnaire survey. The questionnaire was distributed to the managers and officials of the Ende Regency Regional Work Unit involved in preparing the budget. The questionnaire distributed was 51 and again filled out completely and can be processed. The data collected is processed using the SPSS program. The statistical method used to test hypotheses is multiple linear regression analysis. The results showed that budgetary participation, accountability accounting and work motivation had a positive effect on managerial performance. Evidenced by the budget participation regression coefficient of 0.812 with a value of t count 2.069> 2.012 and a significance level of 0.044 <0.05, responsibility accounting for 0.295 with a value of t count 2.152> 2.012 and a significance level of 0.037 <0.05. While the work motivation of 0.620 with a t value of 2.493> 2.012 and the level of significance) 0.016 <00.5.